А kinеtiс аnаlysis fоr prоduсtiоn of саlсium bоrоgluсоnаtе frоm colemanite. Issue 11 (25th June 2020) - Demir, Fatih; Al‐Ani, Anas Osamah Ali; Lacin, Omer
Abstract: In this paper, the kinetic model of colemanite dissolution in gluconic acid solutions was carried out in a batch reactor. The effects of the particle size, reaction temperature, stirring speed, gluconic acid concentration, and solid/liquid ratio on colemanite dissolution were experimentally studied. The empirical parameters were the gluconic acid concentration (0.05‐0.2 M), the temperature (20‐50°C), the solid/liquid ratio (0.05/500‐1.5/500 g⋅L −1 ), particle size (193.5‐1000 μm), and stirring speed (400‐700 rpm). The kinetic models for heterogeneous solid‐liquid reactions were used with the dissolution data in evaluating the kinetic. The dissolution of colemanite in gluconic acid solutions was controlled by diffusion through the product layer. The activation energy was found to be 8.39 kJ⋅mol −1 . The rate expression associated with the dissolution rate of colemanite depending on the parameters chosen may be summarized as follows: 1 − 3 ( 1 − X ) 2 / 3 + 2 ( 1 − X ) = 1.2 e − 8.39 / R T t .